PENERAPAN METODE PROCESS COSTING DALAM PENENTUAN HARGA POKOK PRODUKSI (HPP) PADA UMKM JAMU KUNYIT AQILLA - Nuril Izzah Dwi Putri Elyansyah; Rahadiani Cecilia Atori; Vinna Gayuh Asih; Adam Rafi Fatchurahman; Mochammad Dimas Nur Aziz; Mochamad Usman Sufi; Dian Fahriani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the cost structure and determine the cost of goods manufactured (COGM) at the Aqilla Turmeric Herbal Medicine SME in Sidoarjo using the process costing method. The research method used is descriptive qualitative by conducting direct observation of the production process during November 2025. The results show that the total production cost to produce 300 bottles of herbal medicine per month is IDR 1,175,000, consisting of raw material costs (IDR 740,000), labor costs (IDR 180,000), and factory overhead costs (IDR 255,000). Based on these calculations, the cost of goods sold per unit is IDR 3,916 with a selling price of IDR 6,000. This MSME is able to generate a profit margin of IDR 2,084 per unit or a total monthly profit of IDR 625,200 with a profit percentage of 53.2% of the total production costs. This study indicates that the Aqilla Turmeric Jamu business has sufficient profitability to sustain its operations.